Bat (Mammalia: Chiroptera) biodiversity in a subtropical inselberg ecosystem of Northeastern Argentina - Argoitia, Maria A.; Cajade, Rodrigo; Hernando, Alejandra B.; Teta, Pablo (Revista de Biología Tropical, 2021)
Introduction: Rocky outcrops influence both micro and macro habitat for plants and animals by increasing the availability and predictability of food, providing shelter, and unique microclimatic conditions. Objective: We describe the bat assemblage in three isolated rocky outcrops and their surrounding pediments, adding new data about trophic guilds and roosts. Methods: We surveyed the bat fauna of Paraje Tres Cerros, Corrientes Province, Argentina, explored 13 sites during 26 field trips, using mist nets and search of roosts. We made an accumulation species curve and calculate inventory completeness. The similarity and composition of different habitats was compared by a non-metric multidimensional scaling (NMDS) and an ANOSIM test. Results: We reported 13 species, with a completeness inventory of the 80 % (Jacknife1), corresponding to the families Vespertilionidae, Molossidae and Phyllostomidae. The insectivorous bats were the best represented guild. We found nine types of roost for eight species in different sites. The analysis expressed low differences in the species composition between both types of habitats in the area. Conclusions: The rocky outcrops and their pediments are important ecosystems for the conservation and diversity of the bats in the region, since their communities are regionally unique.